Newspaper «Zvyazda»: clarification of the history of the period of the Great Patriotic War - Kanyuta, Kanyuta I. (Journal of the Belarusian State University. Journalism, 2021)
Тhe military history of one of the most influential publications of the Republic of Belarus newspaper «Zvyazda» is being investigated. The method of historical research helps to restore littleknown facts, to introduce new ones into a historical circulation. Some additional information based on the study of archival documents and materials is supplemented into the biography of the first editor of the underground newspaper «Zvyazda» Vladimir Omelyanyuk, Hero of the Soviet Union. Objec tively covering the events of the Great Patriotic War, the newspaper made a significant contribution to the fight against the German fascist invaders. Studying publishing activity of «Zvyazda» during the war period is especially relevant in the situation when there are numerous attempts to falsify the historical facts and events of World War II.
Keywords: journalism; the newspaper «Zvyazda»; Minsk underground; historical investigation; World War II